Awareness among students, teachers and parents on safety compliances in primary and secondary schools in Malaysia / Malar Kandasamy - Malar, Kandasamy (2018)
The main reason safety system is being implemented is to reduce or prevent accidents and incidents from happening in any workplace. This is done by practising successful safety practise in the said workplace. The implementation is made easy by complying local law, regulations, requirements, guidelines, and code of practices that has long implemented by the government of Malaysia. These sets of law have long been practised by industries in Malaysia, but schools. The main objective of this study is to evaluate the awareness of selected group of people on safety practices in selected schools in Malaysia. A few groups of people were selected and given survey that comprises sets of questions related to safety in schools. Besides the survey, interview was conducted on the selected group of people to further understand their awareness and concern on safety compliances in school. The result shows that the selected group of people has 100% agreed that it is important to implement safety practices in schools but the awareness on what and how it is to be done is still low. Thus, a safety framework that can be made as a part of school education syllabus and training module is established in this study.